Exploring Elementary School Student's Computational Thinking In Terms Of Cognitive Style - Suwarno, Bambang Adi; Masduki, Masduki (Universitas Wiralodra, 2024)
Mathematics learning in the independent curriculum emphasizes the pedagogical dimension which aims to create active students so that they are able to develop their thinking patterns and get them used to finding solutions to their own problems. This study uses qualitative methods to investigate elementary school students' abilities through computational thinking, focusing on the cognitive styles of Field Independence (FI) and Field Dependence (FD). The subjects in this study amounted to 14 fifth grade students of public elementary schools in Klaten Regency, Central Java Province. Researchers used data collection instruments in the form of test, learning style questionnaires and interviews. The number of test compiled consisted of 5 items. Before use, the test were validated by 3 mathematics education experts and tested on 5 fifth grade students. After validation and testing, the test that can be used consist of 3 test. Based on the results of tests and learning style questionnaires, research took one of the students' test results with a Field Independent learning style and 1 student with a Field Dependent learning style. The results of this study indicate that there are differences in the computational thinking process of the two subjects in solving problems. At the abstraction stage, FI students are able to answer important factors that need to be considered in making conclusions, FI students are also able to explain alternative solutions to the problems given appropriately. Meanwhile, FD students tend to work directly so they tend to experience errors at the pattern recognition, algorithm thinking and generalization stages. Thus, it can be concluded that students with a field independent cognitive style are more active in using computational thinking processes than students with a field dependent cognitive style.